2020
DOI: 10.1155/2020/5016916
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Genetic Risk Factors for Diabetic Macular Edema and the Response to Treatment

Abstract: Diabetic retinopathy (DR) is the most common microvascular complication of diabetes mellitus (DM). DR is complex and the term encompasses several clinical subtypes of diabetic eye disease, including diabetic macular edema (DME), the most frequent cause of central vision loss in DR patients. Both genetic and environmental factors contribute to the pathophysiology of DR and its subtypes. While numerous studies have identified several susceptibility genes for DR, few have investigated the impact of genetics on DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…In addition, DMO is a highly complex disease and there may be other unexplored causes of poor outcomes in DMO patients, including genetic, epigenetic and environmental factors. 36 This study is consistent with a similar study by Wecker et al 37 They reported a higher proportion of RVO patients (24%) gained more than 15 ETDRS letters than DMO (13.9%) or nAMD (14.1%) patients after 12 months. While the proportion of nAMD and RVO patients with 15 letters improvement was higher in our study (RVO:43%, nAMD:32%), fewer of our DMO patients (5%) reached this goal.…”
Section: Open Accesssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, DMO is a highly complex disease and there may be other unexplored causes of poor outcomes in DMO patients, including genetic, epigenetic and environmental factors. 36 This study is consistent with a similar study by Wecker et al 37 They reported a higher proportion of RVO patients (24%) gained more than 15 ETDRS letters than DMO (13.9%) or nAMD (14.1%) patients after 12 months. While the proportion of nAMD and RVO patients with 15 letters improvement was higher in our study (RVO:43%, nAMD:32%), fewer of our DMO patients (5%) reached this goal.…”
Section: Open Accesssupporting
confidence: 92%
“…In addition, DMO is a highly complex disease and there may be other unexplored causes of poor outcomes in DMO patients, including genetic, epigenetic and environmental factors. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be intuitive to hypothesize that EPO gene polymorphisms could be involved in the susceptibility to DME. However, few studies have investigated the association of genetic variants with DME [ 44 , 45 ] and Abhary et al [ 11 ] were the only ones who reported the association of EPO polymorphisms with DME. In their study, the minor alleles of the rs1617640 (G), rs507392 (C), and rs551238 (C) polymorphisms were associated with the increased risk of DME in Australians with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study that performed GWAS to differentiate between bevacizumab responders and non-responders, the majority of expressed genes were in transcriptional regulation or receptor activation pathways 19 . A recent study in a Middle Eastern population investigated the relationship between serum hyperglycemia-related long www.nature.com/scientificreports/ noncoding ribonucleic acid (lncRNA) levels and response to anti-VEGF (aflibercept) injection, but no significant association was found 20,21 . To date, only one recent report has conducted a GWAS to identify genes associated with the response to anti-VEGF treatment in DME, which has been performed in the Australian population 22 .…”
Section: Discussionmentioning
confidence: 99%